2009
DOI: 10.1111/j.1365-2826.2009.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Microglia Containing Cyclooxygenase‐1 in the Accumulation of Gonadotrophin‐Releasing Hormone in the Preoptic Area in Female Rats

Abstract: Prostaglandins (PGs), especially PGE(2), are involved in the hypothalamic control of gonadotrophin-releasing hormone (GnRH) release, acting at least in part on the terminal of GnRH axons in the median eminence. The present study aimed: (i) to clarify the role of PG(s) in regulating GnRH cell function at the level of the perikarya in the preoptic area; (ii) to determine the cyclooxygenase (COX) isozyme responsible for producing PG(s) that regulates GnRH perikarya; and (iii) to identify cell types that contain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Importantly, a half of microglia was not immunoreactive for COX-1, thus an anatomocal study between microglia and GnRH might be interesting. The present study confirmed COX-1 immunoreactivity in the POA: COX-1 immunoreactivity was observed in the vicinity of GnRH cells, but was not found within GnRH cells themselves, as shown in the previous study [13].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Importantly, a half of microglia was not immunoreactive for COX-1, thus an anatomocal study between microglia and GnRH might be interesting. The present study confirmed COX-1 immunoreactivity in the POA: COX-1 immunoreactivity was observed in the vicinity of GnRH cells, but was not found within GnRH cells themselves, as shown in the previous study [13].…”
Section: Discussionsupporting
confidence: 77%
“…Since COX-1 immunoreactivity was not found within GnRH neurons and almost entirely doubled-labelled with CD11b, COX-1-expressing microglia would be away from GnRH neurons [13]. Importantly, a half of microglia was not immunoreactive for COX-1, thus an anatomocal study between microglia and GnRH might be interesting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GnRH neurons have been shown to receive neuronal information from several basic neurotransmitter systems of the brain [11,12]. They also communicate with microglia and astroglia [13,14,15,16] and process remote metabolic signals originating from different peripheral tissues/organs of the body [17,18,19]. Events that interfere with the pulsatile secretion of GnRH [20] inhibit reproduction [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%